How A Betawinese Family Implement Politeness in Their Daily Conversation - Winiharti, Menik; Salihah, Triana Salihah (Lingua Cultura, 2017)
Betawi language still exists today. It is particularly used in the suburb area of Jakarta. The typical of this language is changing the suffix /a/ to /e/, as in the words 'siape', 'di mane', 'ade ape', and 'kenape'. The emphasis of suffix /e/ in Betawi language makes this language sound louder or sharper. However, people who are unfamiliar with Betawi ethnic and its language and rarely hear the conversation in Betawinese, usually assume that Betawi language is rude. The paradigm in the society is corroborated by the use of ‘lu’ and 'gua' as the synonyms of 'you' and ‘I’ respectively. In terms of conversation in a Betawinese family, politeness plays a significant role. Every member of the family uses the strategy of politeness. The goals of this study are to find the politeness strategies used by the members of a Betawinese family in their daily conversation. It is also expected to describe the extent to which the family members apply politeness in everyday conversation. The research is conducted by observing the family members when they speak to other members. The data are analyzed based on the speaker and addressee in applying the politeness strategy. The result shows that there are four politeness strategies used: Bald on record, Off record, Positive politeness and Negative politeness. The speakers who have a higher status in the family potentially threaten the 'face' of the hearers who have a lower status. This study has also found that the selection of politeness strategies is determined by two factors; (a) the status of the family members within the family itself and (b) the intensity of inter-speaker meeting. Generally, it is proven that a Betawinese family apply politeness strategies in their daily conversation. Keywords: Politeness strategy, family member, family status, conversation